Evaluation of Aqueous Seed Extracts of Garcinia Kola and Allium Sativum in Hair Loss Reduction - Otasanya, Yemisi (International Journal of Scientific Research in Biological Sciences, 2024)
Aim: The medicinal effect of a mixture of aqueous seed extracts of Garcinia Kola and Allium Sativum extracts, applied directly to the scalp of West African females with type 4B and 4C Afro textured hair and their impact in reducing hair shedding/loss over the period of application was investigated in this study. Experimental Design: A placebo human study, enrolling nine participants from West Africa between the ages 15 and 52, were used as the experimental subjects for this study. Subjects were divided into 3 groups (A-C) with group A as the control having 2 females and 1 male, applying no solution to their scalp or hair. The females had sewed in braids and the male was low-cut. Group B was the test group with the aqueous seed extracts applied directly on the scalp and hair strands, and had 2 females and 1 male, while Group C maintained their existing hair cleansing routine, had 3 females and was used as the placebo. Hair loss was analyzed through observation. Hair shedding and breakage was calculated, monitored and recorded. Place and Duration of Study: The research work and administration of the extracts was carried out at the homes of the participants in Lagos, Nigeria for a period of two months. Methodology: Nine West Africans of both male and female sexes between the ages of 15 and 52 and with Afro-textured type 4B and 4C hair were selected for the research. Treatment was done on Group B, with 250mls of Administration of the extracts applied directly to their scalp every 3 days between the hours of 6am to 8am, with the hair braided and left for 10 minutes, after which it was rinsed off with clean water. The extract was not applied to Group A (Control) and Group C (Placebo). Measurements of the amount of hair fall and shedding was carried out every 2 weeks for a period of 2 months for all groups.